Electrochemical impedance spectroscopy characterization of nanoporous alumina dengue virus biosensor - Nguyen, Binh Thi Thanh (2013)
The Faradaic electrochemical impedance technique is employed to characterize the impedance change of a nanoporous alumina biosensor in response towards the specific binding of dengue serotype 2 (Denv2) viral particles to its serotype 2-specific immunoglobulin G antibody within the thin alumina layer. The optimal equivalent circuit model that matches the impedimetric responses of the sensor describes three distinct regions: the electrolyte solution (Rs), the porous alumina channels (including biomaterials) (Q1, R1) and the conductive electrode substrate layer (Q2, R2). Both channel resistance R1 and capacitance Q1 change in response to the increase of the Denv2 virus concentration. A linear relationship between R1 and Denv2 concentration from 1 to 900 plaque forming unit per mL (pfu mL− 1) can be derived using Langmuir–Freundlich isotherm model. At 1 pfu mL− 1 Denv2 concentration, R1 can be distinguished from that of the cell culture control sample. Moreover, Q1 doubles when Denv2 is added but remains unchanged in the presence of two other non-specific viruses — West Nile virus and Chikungunya virus indicates biosensor specificity can be quantitatively measured using channel capacitance.